2000
DOI: 10.1038/35016111
|View full text |Cite|
|
Sign up to set email alerts
|

Embryonic lethality in mice homozygous for a processing-deficient allele of Notch1

Abstract: The Notch genes encode single-pass transmembrane receptors that transduce the extracellular signals responsible for cell fate determination during several steps of metazoan development. The mechanism by which extracellular signals affect gene transcription and ultimately cell fate decisions is beginning to emerge for the Notch signalling pathway. One paradigm is that ligand binding to Notch triggers a Presenilin1-dependent proteolytic release of the Notch intracellular domain from the membrane, resulting in lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
243
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(250 citation statements)
references
References 28 publications
7
243
0
Order By: Relevance
“…Limited proteolysis of APP CTF-α, CTF-β, N-cadherin and Notch1 was also hampered in the homozygous knockin embryos, although the γ-secretase components appeared to have been properly assembled to a 360 kDa complex. Based on previous studies, it appears that the disturbance in Notch1 processing represents the primary cause of the premature death that we observed 16,35 . Compared to PS1 knockout, the embryonic lethality of PS1-R278I knockin mice occurs at a slightly later stage.…”
Section: Discussionmentioning
confidence: 60%
“…Limited proteolysis of APP CTF-α, CTF-β, N-cadherin and Notch1 was also hampered in the homozygous knockin embryos, although the γ-secretase components appeared to have been properly assembled to a 360 kDa complex. Based on previous studies, it appears that the disturbance in Notch1 processing represents the primary cause of the premature death that we observed 16,35 . Compared to PS1 knockout, the embryonic lethality of PS1-R278I knockin mice occurs at a slightly later stage.…”
Section: Discussionmentioning
confidence: 60%
“…2e–g). Interestingly, Notch1-KO cells expressing TMD-ICD harboring a point mutation that prevents cleavage of the ICD (V1754G 19 , Extended Data Fig. 6b) failed to rescue barrier function (Fig.…”
mentioning
confidence: 98%
“…For example, gene deletion studies in both zebra fish and mice have demonstrated a potential role for Notch signaling in hematopoietic and endothelial development. [4][5][6]8,9,25,39 In addition, both Notch1 and Jagged1 are implicated in the induction of definitive over primitive hematopoiesis. 4,16,25 Notch1-deficient mouse embryonic stem cells contribute to primitive yolk-sac hematopoiesis in chimeric mice but are incapable of adult blood development, 4 whereas Jagged1 is required for the establishment of definitive mouse hematopoietic precursors.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11] In the hematopoietic system, Jagged1 25 and Delta1 14,26 are key regulators of Notch signaling. Accordingly, to understand the role of Notch signaling in human, we examined whether Jagged1 (Jag1) and Delta1 (Dll1) contribute to hematopoietic development from hPSCs.…”
Section: Notch Ligands Via Hes1 Induce Hematopoietic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation